Donor requests for economic analysis of humanitarian field programmes. Issue 7 (3rd October 2018) - Puett, Chloe; Salpéteur, Cécile
ABSTRACT: Humanitarian organisations respond to increasing donor requests to assess economic aspects of their programmes, including cost-effectiveness. This article presents results from a survey of humanitarian agency staff and donor agencies, investigating such requests. Findings indicate a need for clear guidelines and capacity building in these economic assessments, expressed by both humanitarian staff and donor agencies themselves. While improving efficiency is important to ensure effective humanitarian response, caution is warranted in adopting overly burdensome and complex assessments of efficiency which are poorly understood by staff requesting and responding to them, the outcomes of which may lead to reductive and decontextualised decision-making.